Civil society and democracy in Africa : critical perspectives - Kasfir, Nelson (London : Frank Cass, 1998)
"This book provides a careful and broad critique of the conventional wisdom in applying the concept of civil society to politics in sub-Saharan Africa, and particularly to democratisation. It examines the ideological roots of the conventional concept, the reasons for the failure of civil society actors, such as the churches, to play their expected roles, the exclusion of marginalised actors, the inability of civil society organisations to act independently of the state and the failure of civil society to contribute effectively to democratising the African state."--Jacket.
The conventional notion of civil society: a critique / Nelson Kasfir -- Uncivil society, capitalism and the state in Africa / Irving Leonard Markovitz -- The social power of religious organisation and civil society: the Catholic Church in Uganda / Ronald Kassimir -- Expanding 'civil society': women and political space in contemporary Uganda / Aili Mari Tripp -- Politics, capital and the state in Sub-Saharan Africa / Roger Tangri -- Civil society, the state and democracy in Africa / Nelson Kasfir.
"This group of studies first appeared in a special issue of the Journal of commonwealth & comparative politics, v.36, no. 2 (July 1998)"--Title page verso.
Includes index.
Includes bibliographical references and index.
Keywords: Since 1960; Civil society; Democracy -- Africa, Sub-Saharan.